Species delimitation in the Trichocentrum cepula (Oncidiinae, Orchidaceae) complex: a multidisciplinary approach. Issue 1 (31st December 2022) - Camelo-Júnior, Antonio E.; Ferreira, Alessandro W. C.; Andrade, Ivanilza M.; Mayo, Simon J.; Nollet, Felipe; Silva, José L.; Barros, Maria C.; Fraga, Elmary; Pessoa, Edlley M.
Abstract : The Trichocentrum cepula complex comprises three species, T. caatingaense, T. cepula and T. sprucei, endemic to tropical forests east of the Andes in South America. The delimitation of these species has been diversely interpreted due to the extensive morphological variation in the complex. We applied an integrative approach to achieve a better understanding of these biological units, using geometric morphometrics, cytogenetic analysis (chromosome counts and CMA/DAPI banding) and molecular phylogenetics (ITS and rpl32-trnL ). An initial morphometric analysis using the pre-identified specimens into three taxa suggested that T. sprucei is distinct from the other two, which show some overlap. A subsequent analysis of the labellum, including only T. caatingaense and T. cepula organized in six pseudo-populations, suggested the existence of four morphological groups. All analysed specimens presented 2 n  = 36 chromosomes, CMA + /DAPI − terminal bands and CMA − /DAPI + pericentromeric bands, which varied in number across species, localities or even individuals from the same locality. The notable variation in DAPI + pericentromeric bands may be related to transposable elements that could also be a factor influencing the wide morphological variation in the flowers. In the phylogenetic analysis, the specimens belonging to T. caatingaense formed a strongly supported clade sister to the rest, whereas the specimens belonging to T. cepula and T. sprucei emerged together, with their relationships tending to be determined by geographic proximity. The evidence we generated suggests that treating the Brazilian populations of this species complex under a single name, T. cepula, provides more taxonomic stability and utility, thus the necessary taxonomic changes are implemented.